Menadione and protocatechuic acid: A drug combination with antitumor effects in murine osteosarcoma cells - Inacio, Kelly Karina; Pessoa, Adriano de Souza; Tokuhara, Cintia Kazuko; Pagnan, Ana Lígia; Sanches, Mariana Liessa Rovis; Fakhoury, Vanessa Svizzero; Oliveira, Gabriela Silva Neubern de; Oliveira, Flavia Amadeu de; Ximenes, Valdecir Farias [UNESP]; Oliveira, Rodrigo Cardoso de (My University, 2024)
Osteosarcoma (OS) is a primary malignant bone tumor that has an abnormal expression of oncogenesis and tumor suppressors and causes dysregulation of various signaling pathways. Thus, novel therapeutic strategies for OS are needed to overcome the resistance of traditional treatments. This study evaluated the cytotoxic and anticancer effects of the association between menadione (MEN) and protocatechuic acid (PCA) in murine OS cells (UMR-106). The concentrations were 3.12 μM of isolated MEN, 500 μM of isolated PCA, and their associations. We performed cell viability assays, morphology modification analysis, cell migration by the wound-healing method, apoptosis by flow cytometry, reactive oxygen species (ROS) production, gene expression of NOX by RT-qPCR, and degradation of MMP-2 and 9 by zymography. Our results showed that the association of MEN+PCA was more effective in OS cells than the compounds alone. The association decreased cell viability, delayed cell migration, and decreased the expression of NOX-2 and ROS. In addition, the MEN+PCA association induced a slight increase in the apoptotic process. In summary, the association can enhance the compound's antitumor effects and establish a higher selectivity for tumor cells, possibly caused by significant mitochondrial damage and antioxidant properties.
Keywords: MEN + PCA association; Menadione; Osteosarcoma; Protocatechuic acid; UMR-106